CAPACITY VERIFICATION OF CONTAINER TERMINAL AT TAP LINE OF A COMPANY IN MLADA BOLESLAV AND PROPOSALS FOR ITS INCREASING (Perner's Contacts, 2009)
The paper deals with comparison of present technology and utilization of container terminal in Mladá Boleslav. There are presented also some capacity extension possibilities and description of transports of disarticulated cars in containers to Russian factory at Kaluga. Those models were made for different capacities of production.
Keywords: container terminal; siding; reach stacker